Conceptualizing ecosystem services using social–ecological networks. (March 2022) - Felipe-Lucia, María R.; Guerrero, Angela M.; Alexander, Steven M.; Ashander, Jaime; Baggio, Jacopo A.; Barnes, Michele L.; Bodin, Örjan; Bonn, Aletta; Fortin, Marie-Josée; Friedman, Rachel S.; Gephart, Jessica A.; Helmstedt, Kate J.; et al.
Abstract : Social–ecological networks (SENs) represent the complex relationships between ecological and social systems and are a useful tool for analyzing and managing ecosystem services. However, mainstreaming the application of SENs in ecosystem service research has been hindered by a lack of clarity about how to match research questions to ecosystem service conceptualizations in SEN (i.e., as nodes, links, attributes, or emergent properties). Building from different disciplines, we propose a typology to represent ecosystem service in SENs and identify opportunities and challenges of using SENs in ecosystem service research. Our typology provides guidance for this growing field to improve research design and increase the breadth of questions that can be addressed with SEN to understand human–nature interdependencies in a changing world. Highlights: Social–ecological networks (SENs) provide a promising approach to represent the complex ecological, social, and social–ecological relationships that influence ecosystems service supply. Ecosystem services can be represented in SENs as nodes, links, attributes, or as emergent properties of the network, each bringing distinct aspects of ecosystem services into focus to address different questions. Applications of SENs in ecosystem service research can foster: (i) understanding of the social and ecological drivers of ecosystem services; (ii) forecasting of the impacts of stressors; (iii) investigation of trade-offs between ecosystem services; and (iv) assessment of the effects of alternative management options. Ecosystem service research would benefit from a typology to conceptualize particular ecosystem services in SEN analyses and from greater clarity of when ecosystem service research can benefit from a SEN approach.